Traumatic fibroma – a review - Rocafuerte - Acurio, Marco Antonio (2019)
The intraoral fibrous growth of the soft tissues is relatively common and may be benign reactive or a neoplastic lesion. Among these localized fibrous growths, it has been found that traumatic fibroma is the most common in the oral cavity. The traumatic fibroma is a reactive fibrous hyperplasia caused by trauma or local irritation, such as the presence of calculus, overhanging margins of restorations, orthodontic appliances, among others. This pathology is also known as irritation fibroma, inflammatory fibroma, focal fibrous hyperplasia, fibrous nodule and fibrous polyp. It can occur anywhere in the oral cavity but it is more frequently seen in the buccal mucosa or along the occlusal plane. Traumatic fibroma is a common lesion in the oral cavity. Therefore, a wide knowledge about this injury would be useful for dentists in the treatment of their patients.